(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Shift work has been found to be associated with various health problems that not only affect workers but also economic and industrial sectors of a country. Disturbance of workers’ normal social or biological diurnal rhythms, or both, cause health problems of shift workers. Objectives: The aim of the study was to compare blood pressure between shift and non-shift physicians. Methods: This cross-sectional type of comparative study was carried out in the Department of Physiology in Rajshahi Medical College over a period of 12 months from January 2022 to December 2022 among physicians of Rajshahi Medical College and Hospital aged 25-35 years. Approval from the Ethical Review Committee (ERC) was obtained prior to the commencement of the study and the sampling technique was purposive. Pre-designed, validated, structured questionnaire was used to gather information from 230 physicians in Rajshahi Medical College and Hospital. Results: The mean age of the shift physicians was 30.36 ± 3.13 years and the non-shift physicians was 29.10 ± 3.17 years. Shift physicians were more likely to be overweight (75.70%) than the non-shift physicians (50.40%) with mean BMI of shift physicians was 26.75 ± 1.10 kg/m2 and non-shift physicians was 25.34 ± 2.31 kg/m2. The mean duration shift work of the physicians was 4.91 ± 2.38 years. Among shift physicians 26.10% were hypertensive, 14.80% were pre-hypertensive and among non-shift physicians 10.40% were hypertensive, 9.60% were pre-hypertensive and there was statistically highly significant relationship between duration of shift work and status of blood pressure of the shift physicians. The mean SBP and DBP in shift physician group were also higher than the non-shift physician group and both of them were statistically significant (p < 0.01 and p < 0.05 for SBP and DBP, respectively). Conclusion: Shift work is associated with greater risk of hypertension in shift physicians in comparison to non-shift physicians. As shift work practice is common in industrialized countries as well as in developing countries, interventions to minimize such risk among physicians need to be introduced. TAJ 2023; 36: No-2: 171-178